2015
DOI: 10.1159/000381299
|View full text |Cite
|
Sign up to set email alerts
|

The Novelty of the 2015 Guidelines of the Taiwan Society of Cardiology and the Taiwan Hypertension Society for the Management of Hypertension

Abstract: The prevalence rate of hypertension in Asian countries grows faster than in other parts of the world, where stroke exceeds coronary heart disease in causing morbidities and mortalities. The optimal management of hypertension is therefore an especially important task in Asia. In a transparent and rigorous guideline development process, the most updated information available on the management of hypertension was summarized in the 2015 Taiwan Society of Cardiology (TSOC)/Taiwan Hypertension Society (TSH) hyperten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Previous studies and guidelines recommend initial combination therapy for early BP control, particularly for patients with BP above 160/100 mmHg or BP 20 mmHg above target BP. 1 7 The rationale for this recommendation is that any standard dose of a single agent will lower BP by 10/5 mmHg, while any combination of standard dose of two antihypertensive drugs will reduce BP by 20/10 mmHg. 8 , 9 It has been reported that BP reduction with antihypertensive drugs is directly related to the baseline BP, 10 , 11 challenging the concept of initial combined administration.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies and guidelines recommend initial combination therapy for early BP control, particularly for patients with BP above 160/100 mmHg or BP 20 mmHg above target BP. 1 7 The rationale for this recommendation is that any standard dose of a single agent will lower BP by 10/5 mmHg, while any combination of standard dose of two antihypertensive drugs will reduce BP by 20/10 mmHg. 8 , 9 It has been reported that BP reduction with antihypertensive drugs is directly related to the baseline BP, 10 , 11 challenging the concept of initial combined administration.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of DM was 28.5 % but increased to 44% among those older than 60 years, which was higher than the DM prevalence in Taiwan (approximately 20% in the population older than 60 years) [17]. The rate of hypertension (HTN) was 35.7% but increased to 55 % among those older than 60 years, which might be similar to the HTN prevalence in Taiwan (47% among individuals aged 60 years) [18]. Heart disease, renal disease and liver disease didn't show positive correlation with type 1 AIP.…”
Section: Discussionmentioning
confidence: 99%
“…This issue of Pulse brings together reviews of new or pending guidelines for the management of hypertension from China, Japan, Korea and Taiwan, covering the vast populations of East Asia [1,2,3,4,5,6,7,8,9]. This is a most timely and welcome initiative for many reasons.…”
mentioning
confidence: 99%
“…One area of difference, compared to the recent western guidelines, is that all four of these Asian guidelines recommend more stringent blood pressure targets for some groups of patients, albeit with some variation amongst these. The Japanese guidelines recommend a retention of the target of <130/80 mm Hg for patients with diabetes or chronic kidney disease and albuminuria [3,7], and the Taiwan guidelines advocate this same target for patients with diabetes and proteinuric renal disease, and additionally for those with coronary disease and those receiving antithrombotic drugs for stroke prevention [5,9]. The Korean guidelines recommend tighter targets for high-risk patients, specifically <140/85 mm Hg for patients with diabetes and <130/80 mm Hg for those with chronic renal disease and prominent albuminuria [4,8].…”
mentioning
confidence: 99%
See 1 more Smart Citation